Counseling supervision post-COVID-19: challenges and experiences of IIUM novice counselors - Kassim, Siti Kholijah; Rais, Haniza; Abd Karim, Aishah Hanim (Fakulti Pengajian Pendidikan, Universiti Putra Malaysia, 2024)
The COVID-19 pandemic, which originated in 2019, has had a profound impact on global education (Onyema et al., 2020), economy, and the physical and psychological well-being of individuals (Alqahtani et al., 2022; Mishra et al., 2020; Naseer et al., 2023). The impacted population include families, organisations, government entities, and students, as well as those in assisting professions such as law enforcement officers, medical practitioners, registered nurses, educators, psychotherapists, and counsellors (Isasi et al., 2021). The training of practicum counselors was restricted due to the movement control order (MCO) enforced by the Malaysian government. The limitations on movements and a ban on social gatherings throughout that time had impacted their training. For instance, face-to-face supervision classes and support groups by the university supervisor cannot be conducted as usual, causing the practicum counselors to have limited consultation regarding their training. Furthermore, due to the nationwide impact of the MCO, schools were temporarily shut down. Even after reopening, the majority of school administrators have declined to accept any applications for practicum and internship opportunities. Consequently, practicum counselors had to conduct counseling sessions among their friends or closed community. The limited opportunity for practical experience during practicum and internship has hindered their professional development and proficiency. Regrettably, little research has been conducted to investigate the extent to which their training experiences during the COVID-19 pandemic impact their performance as novice counselors. This qualitative research used the phenomenological approach to investigate the challenges and experiences faced by IIUM Novice Counselors during their first posting following the pandemic. A semi-structured interview was done with four novice counselors who were chosen via the purposive sampling method with a few inclusive criteria. The findings indicated that the challenges faced by the school counselors mostly centred on their obligations as professional counselors, their adjustment to changes in employment responsibilities due to the pandemic, their assimilation to unfamiliar surroundings and environments, their adaptability to cultural differences, and their financial capabilities. The researchers further discovered that the chosen novice counselors effectively overcame their challenges by mutually empowering one another and obtaining substantial support from their friends, family, senior counselor, and school administrators.